Multi‐path unequal clustering protocol based on ant colony algorithm in wireless sensor networks. Issue 2 (1st March 2020) - Wang, Weijing; Tong, Guoxiang
Abstract : For the requirement of low power consumption in wireless sensor networks, from the point of view of prolonging the life cycle of the whole network and improving the utilisation rate of the network, this study proposes a LEACH‐EA protocol based on LEACH algorithm. In order to increase the probability of being elected as a cluster head node so that more nodes in the network can share the transmission energy equally, the residual energy factor and the influence factor of node distance are added to the cluster head election threshold. Considering the energy loss of single‐hop transmission and the limitation of single‐hop transmission on the maximum transmission distance of equipment, the ant colony algorithm is used to find the optimal transmission path for nodes iteratively. Finally, by comparing with LEACH, MODLEACH, LEACH‐GA, simulation experiments show that LEACH‐EA protocol has significantly improved in network life cycle, total network data transmission and cluster head number. The network utilisation rate of LEACH‐EA is 431.3, 135.7 and 38.6% higher than the other three algorithms, respectively.